Advanced Radio Resource Allocation Schemes for Multi-Service Wireless Networks - Dafalla, Zubeir Izaruku (2009)
The main focus of this thesis is on heterogeneous resource allocation with emphasis on power control algorithms. Power control is of utmost importance in CDMA cellular radio systems. These systems are targeted for a large number of subscribers and high speed wireless multimedia services. The increasing bandwidth demands and the growing number of users call for efficient radio resource management, and thus power control, as an important part of RRM, needs to be carefully considered.